The (COSO) Framework: Implications of Internal Control Components on the Performance Manufacturing Companies - Sardar Jalal Braim; Rebin Bilal Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The study examines the implications of internal control components on risk assessment using the Committee of Sponsoring Organizations (COSO) framework on manufacturing companies in Erbil, Kurdistan. A multivariate analysis was applied on 250 responses in modelling the individual effects of internal control components (control environment, risk assessment, control activities, information and communication, and monitoring) on risk assessment. The results of the study indicated that the integrated internal control environment, risk assessment, control activities and monitoring components have significant positive effects on organisational performance compared to information and communications. The present study advances the literature on internal control as corporate governance and performance-enhancing tool. Additionally, it also advances internal control’s conceptual framework on organisational performance. Lastly, the results of this study advance construct and item development involving internal control components and organisational performance while testing relationships to uncover the significance of their implications in enhancing organisational performance